THE ROLE OF ARTIFICIAL INTELLIGENCE IN ECONOMIC TRANSFORMATION: FROM AUTOMATION TO THE DATA ECONOMY - Viktoriia Mykytas (Three Seas Economic Journal, 2025)
The purpose of this paper is to explore the transformative role of artificial intelligence (AI) in shaping the structure and dynamics of modern economies. Particular attention is given to AI’s impact on labor markets, the evolution of new professions, and the development of human capital. As AI technologies continue to permeate production, services, and public administration, they are reshaping not only economic processes but also the very nature of work and professional identity. The primary objective of this research is to identify both the strategic opportunities enabled by AI integration and the key risks it poses, especially in terms of employment disruption, technological inequality, and ethical challenges. In doing so, the paper proposes frameworks for sustainable and inclusive adaptation to the AI-driven economy. Methodology. The study is based on a comprehensive literature review combined with the analysis of recent statistical data and forecasts from leading international organizations, such as the World Economic Forum, the World Bank, and the International Labor Organization. To capture the practical implications of AI transformation, comparative and sectoral case studies are employed, focusing on industries including manufacturing, logistics, finance, healthcare, and agriculture. These are supplemented by empirical indicators related to education, employment, and technological adoption. Results. The study finds that AI significantly accelerates automation, transforming both manual and cognitive labor by replacing repetitive tasks and supporting decision-making processes. This transition reduces the demand for low-skilled labor while increasing the demand for highly specialized professionals in AI development, data analysis, AI ethics, and cybersecurity. However, it also raises profound concerns related to job displacement, unequal access to retraining, data privacy, and algorithmic transparency. The development of human capital through lifelong learning, digital upskilling, and educational reform is identified as a core component of economic resilience in the AI era. Additionally, the emergence of remote and hybrid work models is reshaping employment practices and necessitating new regulatory frameworks. The paper emphasizes that successful integration of AI into economic systems requires a balanced approach that promotes innovation while safeguarding social cohesion. Governments, businesses, and educational institutions must collaborate to ensure that the benefits of AI are broadly shared and that societies remain adaptable in the face of accelerating technological change.